The design and implementation of a web ontology for personal learning environments - Aguilar, Emerico H. (College of Engineering, University of the Philippines Diliman, 2014)
The concept of a Personal Learning Environment (PLE) has become an increasingly discussed topic in the domain of learning over the past few years. It is valued not only for its pragmatic approach towards acquiring knowledge, but also for its potential to reach a large number of users. Such views can be largely attributed to the fact that PLEs take advantage of the facilities provided by the Internet. In particular, PLEs use the Web as its primary medium for providing personalized learning through its wide collection of information and applications. However, the lack of structured knowledge representation in the Web can hinder PLEs from reaching their full potential. The Semantic Web, though, may be used to deal with this shortcoming. Its driving principles and technologies may be applied to allow PLEs to reach a level of interoperability that was previously not possible. This study proposes a web ontology and an infrastructure that would enable PLEs to capitalize on the advantages provided by the Semantic Web.